A revisão da ontologia como fenomenologia da vida em Merleau-Ponty - Mantovani, Harley Juliano (2017)
The fundamental purpose of our work was to think a phenomenology of life from the revision of the classic ontology that was designed by Merleau-Ponty. The phenomenology of life required a thought free of the weight of the theoretical structure of classical ontology. For this reason, the phenomenology of life is not initially ready and available in the philosophy of Merleau-Ponty, but rather, it develops and presents itself through the progressive identification of this philosophy with a project of ontology renewal that begins by showing the conditions of the crisis of contemporary philosophy. The emergence of the need to think of life as the supreme and ultimate question of philosophy, besides denouncing a philosophical deviation from a rationalist inversion, reveals that philosophy did not triumph, on the contrary, if life is understood as the existential eternity of a residue, the thought of life demands that philosophy be a perpetual beginning initially dispossessed of all separate and absolute divinity. The return to a humble beginning, which life expects of us, means to get rid of the vanity of an understanding that leads us to the nihilism that characterizes the forgetting of origins, therefore, only a heroic reason achieves the humility of the beginning, and it was this heroism of a responsible reason that Husserl's phenomenology offered to the ontological project of Merleau-Ponty. If the thought of life necessitates the heroic search for the humility of the beginning, then it presents us the nouvelle ontologie as an Ursprungsklärung which, illuminating the birth of the Logos prior to the idealization of science, leads us to a Naturphilosophie which shows us that the phenomenology of life can not suffer the idealistic rupture of nature, man and God that exists only in the knowledge that constructs labyrinths as rational beings. Finally, based on the humility and heroism of thought en naissance, the phenomenology of life represents the victory over the mythological labyrinth of naturalism, humanism and theism.